Frailty and neuropathology in relation to dementia status: the Cambridge City over-75s Cohort study. (15th October 2021) - Wallace, Lindsay; Hunter, Sally; Theou, Olga; Fleming, Jane; Rockwood, Kenneth; Brayne, Carol
ABSTRACT: Objective: To examine the relative contributions of frailty and neuropathology to dementia expression in a population-based cohort study. Design: Cross-sectional analysis of observational data. Setting: Population-representative clinicopathological cohort study. Participants: Adults aged 75+ recruited from general practice registries in Cambridge, UK, in 1985. Measurements: A 39-item frailty index and 15-item neuropathological index were used to operationalize frailty and neuropathology, respectively. Dementia status was ascertained by clinical consensus at time of death. Relationships were evaluated using logistic regression models in participants with autopsy records ( n = 183). Model fit was assessed using change in deviance. Population attributable fraction for frailty was evaluated in relation to dementia incidence in a representative sample of the survey participants ( n = 542). Results: Participants with autopsy were 92.3 ± 4.6 years at time of death, and mostly women (70%). Average frailty index value at last survey before death was 0.34 ± 0.16. People with dementia (63% of the sample) were frailer, had lower MMSE scores, and a higher burden of neuropathology. Frailty and neuropathological burden were significantly and independently associated with dementia status, without interaction; frailty explained an additional 3% of the variance in the model. Assuming a causal relationship and based on population-attributable fraction analyses, preventing severe frailty (Frailty Index ≥ 0.40) could have avoided 14.2% of dementia cases in this population-based cohort. Conclusions: In the very old, frailty contributes to the risk for dementia beyond its relationship with the burden of traditional dementia neuropathologies. Reducing frailty could have important implications for controlling the burden of dementia. Future research on frailty interventions should include dementia risk as a key outcome, public health interventions and policy decisions should consider frailty as a key risk factor for dementia, and biomedical research should focus on elucidating shared mechanisms of frailty and dementia development.